The impact of the development of the tourism sector in terms of economic, social population and land cover in Batu City - Fardiah Qonita Ummi Naila (Jurnal Pariwisata Pesona, 2023)
The development of the tourism sector has a positive impact on city growth through increased profits and revenues, encouraging competition from city managers in increasing tourist attraction through facilities, investment, employment, and local income. The development of tourism-supporting infrastructure accelerates city growth by increasing population, economic interaction, and land cover transformation. This study identifies the relationship between tourism development, economic transformation, socio-population, and land cover. The 2016-2021 constant price GDP shift-share analysis is used to understand economic transformation, while the 2020-2021 population growth and population density analysis for social aspects. As a result, the socio-population aspect shows a transformation in Batu City, where manufacturing business has shifted to service business as the main occupation, which has an impact on increasing population growth. In land cover, significant changes are seen in built-up, open, plantation, and forest. This research provides a preliminary analysis of the development of the tourism sector from the economic, socio-population, and land cover aspects in 2016-2022. These transformations reflect dynamic changes in the city's economic and social structure, requiring continuous monitoring for better policies.